COMPUTERS SELF-EFFICACYS, COMPUTERS ANXIETYS, AND ATTITUDES TOWARD COMPUTERS (BEHAVIOR) BANKING EMPLOYEES IN USING INFORMATION TECHNOLOGY IN SEMARANG - Suhartono, Entot; Anissa, Nur (PRESTASI, 2009)
The purpose of this study is to examine and analyze about behavior banking employees in using information techonology in Semarang. The behavioral used in this study concerns on computer self efficacy, computer anxiety and attitudes toward computers . This study evaluate to relationship between computer self efficacy with attitudes toward computers and the relationship between computer anxietyÂ  with attitudes toward computers. This studyâs goal is to know the effect of computer self efficacy with attitudes toward computers and the effect of computer anxiety withÂ  attitudes toward computer. This study uses survey method, that is by using questionnaires amounting 104 to be sample. Statistic tool used is reliability and validity test to examine whether the questionnaires used are valid and realiable. Pearson correlation is used to examine the relationship between variables and simple regression to examine the effect among variables. To help its statistic and the analysis, the current study uses MS Excel and SPSS version 10 program. Based on data analysis, it is concluded that there is relationship between computer self efficacy and attitudes toward computers banking employees in using information technology in Semarang, there is indicate with r pearson correlation 0.918 and significany value less then 0.05. It is concluded that there is relationship between computer anxiety and attitudes toward computers banking employees in using information technology in Semarang, there is indicate with r pearson correlation -0.962 and significany value less then 0.05. It is concluded that there is effect between computer self efficacy on to attitudes toward computers banking employees in using information technology in Semarang, there is indicate with r determination R Square 84.3% (0.843) and significany value less then 0.05. It is concluded that there is effect between computer anxiety on to attitudes toward computers banking employees in using information technology in Semarang, there is indicate with r determination R Square 92.5% (0.925) and significany value less then 0.05. Keywords :Â  computer self efficacy, computer anxiety, attitudes toward computersÂ